Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/acer.14140
|View full text |Cite
|
Sign up to set email alerts
|

Specifically Sized Hyaluronan (35 kDa) Prevents Ethanol‐Induced Disruption of Epithelial Tight Junctions Through a layilin‐Dependent Mechanism in Caco‐2 Cells

Abstract: Background: Specific-sized species of the carbohydrate hyaluronan elicit a variety of cellular responses mediating tissue integrity and repair, as well as regulating inflammatory responses. Orally provided hyaluronan with an average molecular weight of 35 kDa (HA35) protects mice from shortterm ethanol (EtOH)-induced liver injury. This protection was associated with maintenance of the colocalization of zonula occludens-1 (ZO-1) and occludin at tight junctions in the proximal colon. However, it is not known whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Also, ZO-1 is a cytoskeletal linker protein that forms cross-links with other transmembrane proteins like occludins, necessary for the connection of other TJ proteins to the cytoskeleton [ 65 ]. The report demonstrated that the administration of 40 mM ethanol to Caco-2 monolayers disrupted the TJs, specifically occludins and ZO-1 [ 66 ]. Also, acute alcohol exposure disrupts the barrier function by downregulating the expressions of ZO-1 and occludin in colons of mice [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, ZO-1 is a cytoskeletal linker protein that forms cross-links with other transmembrane proteins like occludins, necessary for the connection of other TJ proteins to the cytoskeleton [ 65 ]. The report demonstrated that the administration of 40 mM ethanol to Caco-2 monolayers disrupted the TJs, specifically occludins and ZO-1 [ 66 ]. Also, acute alcohol exposure disrupts the barrier function by downregulating the expressions of ZO-1 and occludin in colons of mice [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…17 Mediators of Inflammation and ZO-1 [66]. Also, acute alcohol exposure disrupts the barrier function by downregulating the expressions of ZO-1 and occludin in colons of mice [18].…”
Section: Discussionmentioning
confidence: 99%
“…Related strategies have included treatment with butyrate, an important fuel source for colonic enterocytes, as well as multiple molecules shown to improve tight junction integrity in the intestine, such as zinc, saturated fatty acids, glutamine, and hyaluronic acid with an average molecular weight of 35 kDa (HA35). [141][142][143][144][145] To date, only zinc supplementation has been tested in patients with AH, used in combination with anakinra and pentoxifylline as part of a large multicenter clinical trial. 146 Hepatocyte injury While PAMPs entering the portal circulation from the gut are one source of inflammatory signals contributing to ALD, DAMPs derived from injured or dead cells are other potential targets for therapeutics in ALD.…”
Section: Microbial Dysbiosis and Intestinal Barrier Functionmentioning
confidence: 99%
“…Related strategies have included treatment with butyrate, an important fuel source for colonic enterocytes, as well as multiple molecules shown to improve tight junction integrity in the intestine, such as zinc, saturated fatty acids, glutamine, and hyaluronic acid with an average molecular weight of 35 kDa (HA35). 141 145 To date, only zinc supplementation has been tested in patients with AH, used in combination with anakinra and pentoxifylline as part of a large multicenter clinical trial. 146 …”
Section: Immunological Mechanisms Of Aldmentioning
confidence: 99%
“…266,267 Other investigations state that HA-35 treatment protects intestinal tight junctions from alcoholinduced barrier damage. 268 Given these findings that HA-35 regulates KC activation and protects gut barrier function, this HA fragment may have therapeutic value for ALD treatment.…”
Section: Potential New Therapies and Targets For Ald Treatmentmentioning
confidence: 98%